IMPROVEMENT OF THE PRODUCTION POTENTIAL MANAGEMENT STRATEGY OF THE HOTEL ENTERPRISE - Свідло, Карина; Завада, Катерина (SWorldJournal, 2023)
The article examines the strategy of managing the personnel potential of the hotel network on the example of the Ukrainian enterprises of the French multinational hospitality company Accor S.A. The stages of formation of strategic management of personnel